Post-activation potentiation influence on sprint acceleration performance - Greenough, D. C. (Journal of Australian Strength and Conditioning, 2017)
This review aimed to highlight the research that is related to the different methods and modalities that a coach can use post-activation potentiation (PAP) during training and pre-competition. Reviews of the literature were conducted using search engines Google Scholar, PubMed and SPORTDiscus with 27 articles meeting the inclusion criteria. Strength levels of an athlete, time between conditioning activity and subsequent exercise were found to influence PAP response. Recent research suggests power cleans may elicit a greater response than a back squat on sprint performance due to similar biomechanics and a larger power output required to perform the power clean. Resisted sprints is researched for the cumulative transfer effects but more research is needed in the acute enhancement of PAP on acceleration. Plyometrics research is mixed with the acute enhancement of PAP for sprint ability. The application of complex/contrast training through a conditioning activity was shown to induce acute improvements ranging from 1.2%-3.5% in sprint performance over 15m-100m. Conditioning activity recommendations include the use of plyometric weighted (10% body mass) bounding for 3 sets of 10 reps, and performing the power clean over multiple sets (2-5) of 3-5 repetitions at >85% 1RM, dependent on training status. Athletes with more than 3 years of resistance training experience appear to respond optimally, as well as a relative back squat strength of 2 x body mass. 7-10 minutes between the conditioning activity and subsequent exercise appears to optimally augment power output, with PAP manifestation appearing to dissipate after 30min post conditioning activity. Athletes can benefit from incorporating PAP into training for sports that require high levels of acceleration, such as soccer, rugby and track sprinting.